PENINGKATAN PEMAHAMAN KONSEP IBADAH GHAIRU MAGHDAH DENGAN MENERAPKAN MODEL EXPERIENTIAL LEARNING - Loliyana Loliyana (Jurnal Ilmu Pendidikan, 2012)
The purpose of this study is to analyze: (1) design lesson planning, (2) the learning process, (3) evaluation system, and (4) increase comprehension of the worship ghairu maghdah consept by applying the model of experiential learning. The method used is the review of the follow- through 3 cycles. Techniques of data collection was done by testing and observation. Quantitative data were analyzed deductively. The research concludes (1) The process of learning is done for students the increase acttivity learning concept of worship ghairu maghdah with experiential learning models. Cycle PGSD class I (55 %), second cycle (75 %) and third cycle (87.5%). BK cycle class I (57.5 %), second cycle (75 %) and third cycle (90 %). (2) Comprehension of the concept of worship ghairu maghdah on students PGSD class with an average value, the first cycle (65), second cycle (75), and the third cycle (85). LB class with an average value, the first cycle (67), second cycle (75) and third cycle (87).Keywords: model experiential learning, processes and comprehension, worship ghairu maghdah